2021
DOI: 10.1111/nhs.12797
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of caring in hospice wards in Shanghai

Abstract: Despite the large number of people with cancer who need hospice care, utilization rates at community hospice service in Shanghai are low. This study aimed to review the care provided in these hospice wards and examine the difficulties in delivering service. Fourteen hospice care providers were interviewed, and the data analyzed using qualitative content analysis. Three themes emerged from the interviews: (i) characteristics of hospice patients, mostly cancer patients at the end-of-life stage (within 3-months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The lowest utilization rate among the 16 districts was less than 20% [ 8 ]. Similar findings were echoed in other studies [ 9 , 10 ]. Thus, the utilization of hospice care is unsatisfactory.…”
Section: Introductionsupporting
confidence: 92%
“…The lowest utilization rate among the 16 districts was less than 20% [ 8 ]. Similar findings were echoed in other studies [ 9 , 10 ]. Thus, the utilization of hospice care is unsatisfactory.…”
Section: Introductionsupporting
confidence: 92%
“…Similar ndings were echoed in other studies [8,9]. Thus, the utilization of hospice care is unsatisfactory.…”
supporting
confidence: 87%
“…A local study found that the di culty of the hospice service came from the aspects of patients and their families, healthcare providers, the healthcare system, and policy and regulations from the perspective of hospice care providers were some factors contributing to the underuse of hospice services [10]. Hospice care providers suggested that the unawareness of hospice care of the patients and their families as well as their unacceptance was a key factor impending their use of hospice care [10]. However, this must be further analyzed from the perspective of the patients and their families.…”
mentioning
confidence: 99%
“…Locating a hospice ward in a community health service center undoubtedly will affect people’s willingness to use the service. Meanwhile, the limited drug supply and medical equipment in the community health service centers also contribute to some families avoiding hospice services in the community [ 19 ]. There seems to be a gap between the patients’ and their families’ preferences and hospice service supply.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have discussed the use of hospice services in Shanghai and the challenges of frontline hospice care providers [ 2 , 17 , [19] , [20] , [21] , [22] , [23] ]. Previous local studies have demonstrated that the community-based, city-covered hospice services have not been fully functioning [ 2 , 19 , 21 , 23 ]. Hospice care should be an inseparable part of the whole healthcare system in the city.…”
Section: Discussionmentioning
confidence: 99%